Students' reflective writing through the use of intranet Wordpress blog / Fairuz Husna Mohd Yusof - Mohd Yusof, Fairuz Husna (2013)
This study investigates students' reflective writing via an intranet WordPress blog. The four types of reflective writing are "Descriptive writing", "Descriptive Reflection", "Dialogic Reflection" and "Critical Reflection". A convenient sampling was used to select 58 undergraduate students of Applied Language Studies: English for Professional Communication. The findings reported that most students used "Descriptive Reflection", followed by "Descriptive writing", "Dialogic Reflection" and "Critical Reflection" in their reflections. The findings also recorded that the students' reflections involved more Reflection-On-Action than Reflection-In-Action. The results also show that there are combinations of two or more types of reflective writing in some reflections. Students reflected more on-action because they did not have sufficient knowledge and skills that enabled them to solve any encountered problems immediately. In their blog writing, the students applied various types of reflective writing that included their feelings, opinions, perceptions and learning experiences. All these new experiences of web-based reflective writing using blogs can lead to important implications for effective instruction and learning strategies.